Effect of Flipped Classroom Strategy on the Performance and Cognitive Style of Senior Secondary School Biology Students in Ogun State, Nigeria - OGUNLEYE, Abayomi Taiwo; ONIFADE, Olabamiji John; OGUNDEJI, Alice Funmilayo; SONDE, Patrick Olanrewaju (Ilorin Journal of Education, 2024)
This research investigated the effects of flipped classrooms on the academic performance and Cognitive style of students in Biology. The study employed a pre-test and post-test quasi-experimental research design. The population of the study comprises all senior secondary in Ogun state and the participants for the study were 89 Senior Secondary School I (SSSI) students of two intact classes which were purposively selected from Odeda local government. The instruments used were a Biology performance test and a cognitive style test. Reliability of the Biology performance test was done using KR-20 and the coefficient was found to be 0.77. The reliability of the cognitive style test was done using Cronbach-Alpha and the coefficient was found to be 0.72. The hypotheses were tested using ANOVA inferential statistics at a 0.05 level of significance. The outcome is that there was a significant difference in the academic performance of students who were opened tothe flipped classroom strategy and lecture method. The study conclude that flipped classroomsare more useful in improving students’ academic performance and cognitive style in biological concepts than traditional teaching methods.